The Role of Teaching Assistance in Enhancing the Learning Motivation of Twelfth-Grade Students in English Literature at SMAN 9 Toraja Utara - Nurhikmah Nurhikmah; sam Hermansyah; Nuraeni Nuraeni; Kasmiati Kasmiati; Fahmi Arif; Utu Sanjaya; Asman Asman (Edumaspul: Jurnal Pendidikan, 2024)
This study aims to examine the role of teaching assistance programs in improving the learning motivation of twelfth-grade students in English Literature at SMAN 9 Toraja Utara. The program, part of the Merdeka Belajar Kampus Merdeka (MBKM) initiative, involves university students assisting teaching activities in schools to support literacy, numeracy, technology adaptation, and administrative tasks. Using a descriptive qualitative approach, data were collected through observation, interviews, and documentation over four months. The findings reveal that the teaching assistance program significantly enhances students' interest and enthusiasm in learning. The use of creative methods, such as learning through games and providing rewards, has proven effective in fostering a positive classroom environment and improving academic engagement. Furthermore, the program allows university students to develop essential skills, including leadership, collaboration, and empathy, while contributing to the improvement of teaching quality in schools. This research highlights the importance of innovative educational strategies to support student motivation and academic achievement.